Family Relationship In Calvin Trillin's About Alice Novel (1963): A Sociological Approach - Wahyuningtyas, Tri; , Dr. Phil. Dewi Chandraningrum, S.Pd., M.Ed; , Titis Setyabudi, S.S, M. Hum (2013)
The major problem of this study is to elucidate how the family relationship is reflected in Calvin Trillin's About Alice. The objectives of the study are to analyze the structural elements of this novel and to analyze this novel based on the sociological perspective. In this study, the researcher uses qualitative research whose data are based on primary source, the novel Calvin Trillin's About Alice and secondary sources, such as Calvin Trillin's biography and other data which deal with the research. In analyzing the data, he applies some approaches. The first, structural analysis approach is used to analyze the structural elements of this novel. They consist of character and characterization, setting, plot, point of view, style, and theme. The second, the sociological approach is used to analyze the relationship between this novel and social condition in England society. The sociological approach is applied in order to have the appropriate analysis and answer the problems. Based on the analysis, the researcher draws some conclusions. First, the novel Calvin Trillin's About Alice was created based on the phenomena of English society in early twentieth century. Second, Calvin Trillin's About Alice shows the conflict in the family relationship between mother and her daughters. The last is through her creation of the character and characterization, setting, plot, point of view, style, and theme. This novel gives a clear description that family relationship is the most important in family life. The role of family can keep stability of a family that can arise good impact for the harmonious relationship between parent and children.